Primary Care Providers' Attitudes Related to LGBTQ People: A Narrative Literature Review. Issue 2 (March 2019) - Aleshire, Mollie E.; Ashford, Kristin; Fallin-Bennett, Amanda; Hatcher, Jennifer
The purpose of this article is to review the current literature describing primary care providers' (PCPs) attitudes related to lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) people. LGBTQ individuals experience significant health disparities, and these inequities may be better understood via an ecological systems framework. PCPs' actual or perceived discriminatory attitudes can lead to suboptimal treatment or health outcomes for LGBTQ people. A review of the literature from 2005 through January 2017 was completed using the Cumulative Index for Nursing and Allied Health Literature and PubMed (Medline) databases. The purpose, sample, measure(s), design, findings, strengths, and weaknesses of each study were examined; and findings were synthesized, summarized, and critically appraised. Eight articles were eligible for review. There was significant heterogeneity in the studies' purposes, research questions, LGBTQ population(s) of focus, and findings. Many PCPs' attitudes toward LGBTQ people were positive, but a minority of each studies' participants had negative attitudes toward LGBTQ people. Stigma and health care barriers negatively affect LGBTQ health. Interventions must address LGBTQ health disparities at the individual, mesosytem, exosystem, and macrosystem levels. Research, education, and practice strategies all must be integrated across socioecological levels as components of a population-based approach to eliminate health disparities for LGBTQ persons.